Hepatobiliary and pancreatic hemorrhage: Technical tools and tricks - Chad G. Ball, MD (Elsevier, 2022)
Ongoing hemorrhage from hepatobiliary and pancreatic injuries continues to daunt even the most experienced surgeon. Despite the widespread centralization of elective hepatopancreatobiliary (HPB) surgery to high-volume centers, HPB trauma remains relatively common and requires a rapid and thoughtful approach [1–13].